1993
DOI: 10.1126/science.8446899
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Model for the Interaction Between Elongation Factor Tu and the Ribosome

Abstract: In the elongation cycle of bacterial protein synthesis the interaction between elongation factor-Tu (EF-Tu).guanosine triphosphate (GTP), aminoacyl-transfer RNA (aa-tRNA), and messenger RNA-programmed ribosomes is associated with the hydrolysis of GTP. This interaction determines the selection of the proper aa-tRNA for incorporation into the polypeptide. In the canonical scheme, one molecule of GTP is hydrolyzed in the EF-Tu-dependent binding of aa-tRNA to the ribosome, and a second molecule is hydrolyzed in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
87
0
3

Year Published

1993
1993
2004
2004

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(98 citation statements)
references
References 30 publications
8
87
0
3
Order By: Relevance
“…The formation of a gram (dry weight) of cells of E. coli has been calculated to require the conversion of 43 mmol of ATP to ADP (24). This calculation underestimates the cost of protein synthesis (35) and ignores the cost of transport of materials other than glucose. Adjusting to include those costs, I estimate the overall cost of synthesis to be 50 to 60 mmol of ATP per g (dry weight), or (for purposes of calculation) about 55 mmol.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of a gram (dry weight) of cells of E. coli has been calculated to require the conversion of 43 mmol of ATP to ADP (24). This calculation underestimates the cost of protein synthesis (35) and ignores the cost of transport of materials other than glucose. Adjusting to include those costs, I estimate the overall cost of synthesis to be 50 to 60 mmol of ATP per g (dry weight), or (for purposes of calculation) about 55 mmol.…”
Section: Discussionmentioning
confidence: 99%
“…similarly to the corresponding residue (Asp'19) in the 3D model of c-H-ras p21 at 1.35 A resolution [9]. Raman spectroscopy confirmed the existence of this hydrogen bond [lo] [12] observed that EF-TuD138N recognizes XTP with an affinity comparable to that of wild-type EF-Tu (EF-Tu wt) for GTP. Less clear is the situation concerning the exocyclic O(6) of the base.…”
Section: Introductionmentioning
confidence: 65%
“…The ohgodeoxynucleotide GTGTTCCTGGACAAATG was used to substitute Asn"' with Asp in EF-TuDl38N [12]. The modified tufA was overexpressed via pTTQl8 under control of the tuc promotor m the RecA.…”
Section: Ef-tunl35d/dl38nmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2:1 stoichiometry between EF-Tu and aa-tRNA, observed at 37°C, has been questioned [7,8,11,12]. However, this controversy about the extended ternary complex has recently been resolved [10,13]: RNAse A protection assays in combination with the quench-flow technique show 1 : 1 stoichiometry at 0°C and 2 : 1 at 37°C, which demonstrates that the stoichiometry of the ternary complex changes with temperature.…”
Section: Introductionmentioning
confidence: 99%